Alexithymia and Emotional Regulation in Higher Education: Implications for Student Self-Awareness - Ismail, Ahmed Mohamed Bani; Abdelrazek, Osama Hasan Gaber (European Journal of Social Science Education and Research, 2026)
Alexithymia, emotion regulation, and self-awareness play a crucial role in influencing students’ psychological well-being and mental health during this critical developmental stage. However, there is a lack of research examining the relationship between these variables among university students at Najran University. Therefore, this study explores the relationship between alexithymia, emotional regulation, and self-awareness among Najran University students using a quantitative approach. The researchers applied the Toronto Alexithymia Scale, the Gross and John Emotional Regulation Scale, and the Al-Ghuli Self-Awareness Scale to a sample of 660 undergraduates (373 males, 287 females). Results indicate a moderate level of alexithymia (3.18), a high level of emotional regulation (3.52), and a moderate level of self-awareness (2.08) among participants. A statistically significant negative correlation exists between alexithymia and both emotional regulation and self-awareness (p < 0.01). The study contributes to planning psychological counseling programs aimed at enhancing emotional expression among university students through self-awareness training and emotional regulation interventions